Experimental research of the critical geometric parameters on subcooled flow boiling in confined microchannels. (January 2018) - Hong, Sihui; Tang, Yongle; Dang, Chaobin; Wang, Shuangfeng
Highlights: Conduct visualization and infrared experiments on microchannels subcooled flow boiling. Investigate the critical geometric parameters on the bubble confinement origination. Clarify the determining factor in bubble transversal growth and elongation behaviors. Reveal the exact effect of operating conditions in the different confined microchannels. Heat transfer capability is compared and analyzed with the infrared thermal image. Abstract: Subcooled flow boiling in microchannels plays a significant role in solving heat dissipation issues in many industrial applications. Nevertheless, the fundamentals of flow boiling and bubble dynamics in confined microchannels are lack of sufficient and clear comprehension, especially considering the effect of the geometric parameters. The present work aims at revealing the critical structural parameter that determines the bubble behaviors and heat transfer performance in the different microchannels. By high speed photography, the features of bubble transversal coalescence and the variations of liquid film thickness in the different microchannels are captured and compared, which strongly proves the theoretical discussion about the effect of the geometric parameters. The experiment results indicate that the bubble transversal growth is linearly dependent on RE 3/2, and determined by the geometric parameter w c 2 h c, while the aspect ratio (AR) plays the decisive role in bubble elongation mode and rate. Meanwhile, with a series of crossover experiments, the influence of the inlet flow rate and heat load on the subcooled flow boiling in confined microchannels are also clearly revealed. By analyzing the heat transfer capability caused by these structural differences, some insights might be provided for the better application of confined microchannels.